Endonasal hemicraniectomy by esthesioneuroblastoma: report of a case - Fagalde, Inés; Rondón González, Gabriel; Ragoni, Ana C.; Portillo, Patricia; Ajler, Pablo; Ruggeri, Carlos S. (Revista del Hospital Italiano de Buenos Aires, 2022)
Esthesioneuroblastoma is a malignant neoplasm that originates from the olfactory epithelium.Treatment is established according to its extension and the histological degree of atypia and may include surgery, surgery more radiotherapy or more chemoradiation therapy.Different surgical approaches have been used, including facial incisions and craniotomy, but with the greater experience acquired with endoscopic sinus surgery and teamwork with the neurosurgeon, endonasal techniques have been developed that make it possible to perform oncological resections in selected patients, with less morbidity, brief hospitalization and without compromising local control of the disease.We describe the clinical case of a patient with an esthesioneuroblastoma with intracranial invasion who was successfully treated by endonasal hemicraniectomy preserving the contralateral olfactory bulb.
Keywords: endonasal hemicraniectomy; endoscopic surgery; esthesioneuroblastoma; skull base